2002
DOI: 10.1292/jvms.64.513
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Cytokine Messenger RNA Expression in Peripheral Blood Mononuclear Cells from Dogs with Canine Demodicosis.

Abstract: ABSTRACT. Using RT-PCR and semi-quantitative PCR, mRNA expression for canine interferon (IFN)-γ, interleukin (IL)-2, IL-4, IL-5, IL-10, tumor necrosis factor (TNF)-α and transforming growth factor (TGF)-β in peripheral blood mononuclear cells (PBMCs) was examined in dogs with or without demodicosis. mRNA expression for IFN-γ as well as TNF-α in dogs with demodicosis (localized (LD) and generalized (GD)) was slightly lower than those in dogs without demodicosis (healthy controls). Expression of IL-5 mRNA in dog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
1
6

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 30 publications
4
22
1
6
Order By: Relevance
“…Recently, Yarim et al have demonstrated marked elevation in circulatory transforming growth factor beta (TGF‐β) 1 concentrations in dogs with GD compared to the healthy ones. TGF‐β mRNA expression in peripheral blood mononuclear cells was higher in dogs with LD than healthy ones, and the key role of TGF‐β in the differentiation of LD and GD was suggested . It has also been demonstrated that dogs with GD have a lower CD4+ /CD8+ T cell ratio than dogs having LD .…”
Section: Resultsmentioning
confidence: 98%
“…Recently, Yarim et al have demonstrated marked elevation in circulatory transforming growth factor beta (TGF‐β) 1 concentrations in dogs with GD compared to the healthy ones. TGF‐β mRNA expression in peripheral blood mononuclear cells was higher in dogs with LD than healthy ones, and the key role of TGF‐β in the differentiation of LD and GD was suggested . It has also been demonstrated that dogs with GD have a lower CD4+ /CD8+ T cell ratio than dogs having LD .…”
Section: Resultsmentioning
confidence: 98%
“…This could indicate an early switch to a TH2-type of help, as IL-4 is a key factor for the differentiation of precursor helper cells into TH2 subsets. Up-regulation of the TH2-type of help has been observed in canine demodicosis, a mite infestation of the skin similar to scabies (Tani et al 2002). An early switch towards a predominant TH2-type of help would explain why we could not find an increased serum concentration of IFN-c in the infected animals (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Ill animals was also evident by the incorporation of dense colored granules (NBT dye granules) in the cytoplasm of the phagocytic cells. A recent study demonstrated that Th2-type response is upregulated in dogs having generalized demodicosis with subsequently increased expression of IL-5 and TGFp mRNA in peripheral blood mononuclear cells (PBMGs), but no significant differences were observed in IL-4 and IL-10 mRNA production (Tani et al, 2002). Increased M(|) phagocytosis in diseased condition may result from an alternative activation of Mcj) by the Th2 cytokines e.g., IL-13 (Gordon, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Increased level of TGFp (potent immunosuppressive cytokine) and other immunosuppressive factors such as prostaglandin fi-om the activated Mcj) during diseased condition (Tani et al, 2002;Taveme and Bradley, 1998) can be accounted for the immunosuppression in generalized demodicosis. Parasites like D. canis secrete large amount of antigens which in turn cause high phagocytic activity and consequent overloading of Mcj) resulting in its impaired antigen presenting capacity (Taveme and Bradley, 1998).…”
Section: Discussionmentioning
confidence: 99%